2013
DOI: 10.1186/1756-3305-6-9
|View full text |Cite
|
Sign up to set email alerts
|

Terrestrial vegetation and aquatic chemistry influence larval mosquito abundance in catch basins, Chicago, USA

Abstract: BackgroundAn important determinant of mosquito-borne pathogen transmission is the spatial distribution of vectors. The primary vectors of West Nile virus (WNV) in Illinois are Culex pipiens Linnaeus (Diptera: Culicidae) and Culex restuans Theobald. In urban environments, these mosquitoes commonly oviposit in roadside storm water catch basins. However, use of this habitat is inconsistent, with abundance of larvae varying significantly across catch basins at a fine spatial scale.MethodsWe tested the hypothesis t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 54 publications
(62 reference statements)
1
42
0
1
Order By: Relevance
“…The mechanisms underlying this pattern are not well understood, but some have suggested the positive effect of habitat diversity on mosquito species diversity [48], [49], or that increased stress and pollution in urban habitats favor certain invasive genera such as Culex , which is more adaptable to a variety of habitats and may competitively exclude other species [50], [51], [52]. We suspect that the urban environments in our study may have had fewer kinds of aquatic habitats that different female mosquitoes could exploit, thus favoring human-adapted mosquitoes such as Aedes aegypti and Culex quinquefasciatus .…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms underlying this pattern are not well understood, but some have suggested the positive effect of habitat diversity on mosquito species diversity [48], [49], or that increased stress and pollution in urban habitats favor certain invasive genera such as Culex , which is more adaptable to a variety of habitats and may competitively exclude other species [50], [51], [52]. We suspect that the urban environments in our study may have had fewer kinds of aquatic habitats that different female mosquitoes could exploit, thus favoring human-adapted mosquitoes such as Aedes aegypti and Culex quinquefasciatus .…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that fallen detritus from these trees is captured in basin sumps and that this captured organic detritus is associated with increased pupal abundance. The association with catch basin mosquito abundance and trees has been made elsewhere (Gardner et al 2013). Certainly the close Figure 2.…”
Section: Discussionmentioning
confidence: 77%
“…This suggests that fallen detritus from these trees is captured in basin sumps and that this captured organic detritus is associated with increased pupal abundance. The association with catch basin mosquito abundance and trees has been made elsewhere (Gardner et al ). Certainly the close proximity of multiple deciduous trees to basins may not always result in high productivity, however, identifying basins located close to deciduous trees could be useful to identify the risk for increased productivity.…”
Section: Discussionmentioning
confidence: 99%
“…In a field survey, infection levels in Ae . triseriatus were not correlated with pH, conductivity or water temperature (Van Rhein et al, ), but field surveys have found wide natural variation in gregarine parasite infection levels (Comiskey, Lowrie, & Wesson, ; Mlynarek, Bert, Haydeé Peralta‐Vázquez, James, & Forbes, ; Van Rhein et al, ), which may partly result from differences in phenolic compounds and concentrations arising from different types and quantities of detritus that accumulate in these aquatic habitats (Earl & Semlitsch, ; Gardner et al, ; Kling, Juliano, & Yee, ; Stoler et al, ).…”
Section: Discussionmentioning
confidence: 99%